Influence of ICT on formation of the civic stand of students in the conditions of globalization and informatization - A B Denisova (RUDN Journal of Informatization in Education, 2015)
In the modern world information space starts possessing substantsionalny qualities and to operate the person as the behavior of the subject depends on his knowledge. ICT are ideal means of the organization of communicative influence, including counterproductive, menacing to interests of national security. Only the subject with a creative and active civic stand which formation has to become the most important task of educational institutions can resist to negative information influence. In article the role of information technologies on formation of a civic stand of studens is discussed.